Tax Review Pajak Penghasilan dan Pajak Pertambahan Nilai PT X Untuk Menilai Kepatuhan Wajib Pajak - Santoso, Elvina Putri; Santoso, Urip (Jurnal Administrasi Bisnis, 2023)
Revenue from the state expenditure budget originating from taxes is very influential on state financing. One of the supports for the growth of tax revenues is taxpayer compliance. One way to measure compliance is by conducting a tax review. In this study, a tax review was carried out using the research object, namely Corporate Taxpayer PT X which had been established since 2007. This company is engaged in wholesale trading selling electronic goods and other spare parts. The taxation aspects that will be examined are all Income Tax and Value Added Tax from 2018 to 2020. From the results of the review conducted, it will be seen the level of company compliance in implementing its tax rights and obligations. The research method used is a descriptive analysis study. This research was conducted by collecting data relating to all aspects of taxation in PT X and comparing the results of the implementation of taxation in PT X with the applicable laws and regulations. The results of the tax review that has been carried out, PT X is still not compliant because there are still errors in calculating income tax Article 21 and delays in depositing income tax Articles 21 and 23.